The Effect Of Profitability, Liquidity, Solvency And Tenure Audit On The Acceptance Of Going Concern Audit Opinions On Transportation Companies Listed On The Indonesia Stock Exchange: Opinion Going Concern, Profitability, Liquidity, Solvency, Audit Tenure - evi_gentiaras_; Fransiska Desta Fitriana; Amelia Fernanda; Imelda Sinaga; Maria Maranatha Gultom (Universitas Pamulang, 2024)
This study investigates the influence of profitability, liquidity, solvency, and audit tenure on going concern audit opinions for transportation companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The research employs logistic regression analysis to assess whether these financial and audit-related variables significantly impact the issuance of going concern audit opinions. Descriptive statistical analysis indicates that profitability, liquidity, solvency, and audit tenure exhibit varying levels of influence on audit outcomes. The findings reveal that profitability does not significantly affect going concern audit opinions, indicating that companies with high profitability do not necessarily avoid such opinions. Liquidity also shows no significant influence, suggesting that the company's ability to fulfill short-term obligations may not be a determining factor for auditors. Similarly, solvency does not exhibit a significant impact, as a higher debt ratio does not automatically indicate a worsening financial condition in the eyes of auditors. Finally, audit tenure is found to be insignificant, highlighting concerns about the potential erosion of auditor independence over extended engagements. These findings support prior studies that demonstrate the limited predictive power of these variables concerning going concern opinions in the transportation sector. This research contributes to the ongoing discourse on audit opinions by emphasizing the need to consider both financial and non-financial factors when evaluating a company’s ability to continue its operations. Future research is recommended to explore additional variables and proxies to better understand the dynamics affecting audit opinions in this sector.